Entrepreneurship on the Threshold of 21st Century - TAN, Wee Liang (Institutional Knowledge at Singapore Management University, 1997)
With this issue we would have joined the world in watching Hong Kong, reknown as an entrepreneurial economy, move across the threshold to mainland Chinese control. In Hong Kong, entrepreneurship moves across a threshold to another environment the conditions of which may be different. There are opposing views whether the situation will be restrictive to entrepreneurship. Entrepreneurs operating in Hong Kong would have made alternative plans and strategies. Only time will tell how the events will unfold, suffice to be prepared for the transition is far better than not to have been.